Manajemen Produksi Konten Media Sosial Pada Divisi Konten Media Baru TVRI Jawa Timur - Balqis, Naila; Aji, Gilang Gusti (The Commercium, 2025)
This study aims to describe the management of social media content production implemented by the New Media Content Division of TVRI East Java. Multiplatform digitalization requires TVRI, as a Public Broadcasting Institution (LPP), to remain relevant to society. Social media has now become an essential part of terrestrial media, requiring TVRI to adapt and innovate by managing social media effectively. This research employs a qualitative research method. Data collection techniques include interviews, documentation, and observation. The researcher conducted interviews with the three members of the New Media Content Division team at TVRI East Java. The object of this research is the social media production management. The results of this study indicate that the management of social media content production in the New Media Content Division of TVRI East Java aligns with the media production management theory proposed by Terry (1992), as follows: 1) Planning involves facilities and infrastructure equivalent to terrestrial sophistication, with fewer human resources and budget compared to terrestrial, and indicators are achieved independently. 2) Organizing reveals that team members come from diverse backgrounds, leading to differences in perspectives on understanding digital media and mindset shifts. 3) Execution is carried out efficiently with a clear time structure. 4) Quality control is conducted before uploading content, and content monitoring is performed to evaluate the achievement of success indicators.